PROSEDUR PELAKSANAAN PERHITUNGAN DAN PENAGIHAN PAJAK AIR PERMUKAAN YANG TERUTANG OLEH BADAN PENDAPATAN DAERAH PROVINSI SULAWESI SELATAN - H. Andi Rustam (Jurnal Bisnis dan Kewirausahaan, 2018)
The purpose of this study is to know the procedure of the calculation and collection of Surface Water Taxes owed to the Regional Income Board of South Sulawesi Province. The data sources used are primary and secondary data. The type and method used is the method of qualitative descriptive comparative analysis, which describes the results of research and discussion and comparing it with applicable legislation.Based on the results of research and discussion, showing that see the description of surface water tax collection by the South Sulawesi Province Income Board, which so far Surface Water Surveillance Billing Procedure It is regulated by the SOP Billing of Regional Taxes on the Board of Directors Decision Regional Revenue of South Sulawesi Province No. 01 / I / TAHUN 2015 on Standard Operating Procedures for Local Tax Billing within the SOP. Billing is done by Ordinary Billing that is by issuing SKPD (Local Tax Assessment Letter) or STPD (Tax Collection Letter Regional) indicates that the awareness of taxpayers in particular the surface water taxpayers run well in South Sulawesi.Dan implementation of surface water tax collection by the Provincial Revenue Board South Sulawesi runs optimally with the implementation based on South Sulawesi Governor Regulation No. 23 of 2011 on Guidelines for Implementation of Regional Regulation of South Sulawesi Province Number 10 of 2010 on Area Tax Special Surface Water Tax